Phylogeography in an “oyster” shell provides first insights into the genetic structure of an extinct Ostrea edulis population - Sarah Hayer (Nature Portfolio, 2021)
Abstract The historical phylogeography of Ostrea edulis was successfully depicted in its native range for the first time using ancient DNA methods on dry shells from museum collections. This research reconstructed the historical population structure of the European flat oyster across Europe in the 1870s—including the now extinct population in the Wadden Sea. In total, four haplogroups were identified with one haplogroup having a patchy distribution from the North Sea to the Atlantic coast of France. This irregular distribution could be the result of translocations. The other three haplogroups are restricted to narrow geographic ranges, which may indicate adaptation to local environmental conditions or geographical barriers to gene flow. The phylogenetic reconstruction of the four haplogroups suggests the signatures of glacial refugia and postglacial expansion. The comparison with present-day O. edulis populations revealed a temporally stable population genetic pattern over the past 150 years despite large-scale translocations. This historical phylogeographic reconstruction was able to discover an autochthonous population in the German and Danish Wadden Sea in the late nineteenth century, where O. edulis is extinct today. The genetic distinctiveness of a now-extinct population hints at a connection between the genetic background of O. edulis in the Wadden Sea and for its absence until today.